Student Moral Development Strategy at MAN 1 City of Serang (Implementation of the Four Ministerial Joint Decree on PTMT) - Robiatul Adawiyah; Wawan Wahyudin; Ali Mukhtarom (Formosa Journal of Sustainable Research, 2022)
Moral issues continue to be in the spotlight and issues attract attention, especially during the pandemic. The impact of the Corona Virus Disease (Covid-19) pandemic is a serious concern throughout the country. This study examines the strategies for developing student morals at Limited Face-to-Face Meetings (PTMT) ahead of the New Normal Period of the Covid-19 Pandemic at MAN 1 Serang City. This is in accordance with government policy on the Decree of the Four Ministerial SKB on PTMT PPKM dated 3 February 2022 in the 2021/2022 Academic Year. The purpose of this study is to find out: (1) moral development is very important during PTMT; (2) strategies for fostering student morals during PTMT; (3) supporting and inhibiting factors in fostering student morals during PTMT at MAN 1 Serang City. The type of research in this thesis emphasizes more on field research through descriptive qualitative research methods carried out at MAN 1 Serang City. Data collection techniques through observation, documentation, and interviews, while data analysis techniques after the data is collected, data reduction, analysis, and draw conclusions. The research results show that; (1) the importance of fostering student morals during PTMT at MAN 1 Serang City provides space to master the targeted basic competencies. (2) strategies for developing morals in MAN 1 Serang City through exemplary methods, habituation, and coercion (if deemed important)